Assessing Water Use in WaterSense‐Labeled Homes and Quantifying the Savings. Issue 4 (3rd May 2022) - Schein, Jonah; Bickmore, Toby; Sovocool, Kent
Key Takeaways: After the local Water Smart Homes program ended in 2020, the US Environmental Protection Agency began the WaterSense‐labeled homes Version 2.0 program, launched as a pilot. The study evaluated indoor and outdoor metered water use of 160 WaterSense‐labeled homes in the Las Vegas metropolitan region. Metered data show that WaterSense‐labeled homes used a median of 44, 000 gpy and exceeded their water savings goal.